Traumatic and Toxic Optic Neuropathies - Huban Atilla (Türk Oftalmoloji Dergisi, 2013)
The clinical characteristics, pathogenesis, and treatment of traumatic and toxic neuropathies are given in this manuscript. (Turk J Ophthalmol 2013; 43: 118-23)